Evolution Study Of Mass Customization And Its SWOT Analysis For Business Management Practices (Journal of Namibian Studies : History Politics Culture, 2023)
This paper checks challenges and prospectus related to mass customization as a management tool for growth of business. The mass production and customize production are two opposite poles for style of production. So, when we going for mass customization that means both extremities are getting balanced and meeting in between somewhere.The firms need some management tool which can enable them to achieve high productivity with lean losses and full customer delight. The managers also believe that along with external customers, the internal customership contains the same weightage of importance. And the challenge is, this management tool should support both external and internal customer delight. The mass customization has capability to cater this challenge of modern managers.The study of literature about mass customization was carried out. And it’s found that while implementing mass customization firms faced many challenges and ripped advantages too. The implementation is done either in all areas of management or for some localized department. For this research paper, based on the literature review Strength, Weakness, Opportunity and Threat (SWOT) analysis is carried out to check out how mass customization can enhance management results in growth of business. A successful implementation of mass customization is not as easy as it looks, but its implementation can be a game changer.Many industries, mainly automobile industries, have already implemented mass customization for supply of parts as they must deliver a product in large numbers. Many other implementations of mass customization are operational today, such as software-based product configurations that make it possible to add and/or change functionalities of a core product or to build fully customized assembled products start to end. These are not perfect mass customization examples in the original sense, but they achieved the point of balance between mass production and customized production.As SWOT analysis reveals there are many strengthening examples and plenty of opportunities waiting to get explored for mass customizations in management domain. The company can create a great impact by developing customer-trusted brands. And this can be done with strategic implementation of mass customization in different domains of management like productivity, resource management, supply chain etc. In the era of industry 4.0, a win-win situation can be achieved by achieving economization of scale and customer delight by implementing mass customization.